Efficient carrier‐injection and electron‐confinement in UV‐B light‐emitting diodes. Issue 1 (12th November 2015) - Kolbe, T.; Stellmach, J.; Mehnke, F.; Rothe, M.‐A.; Kueller, V.; Knauer, A.; Einfeldt, S.; Wernicke, T.; Weyers, M.; Kneissl, M.
Abstract: The effects of the aluminum content x and the magnesium doping concentration in the Al x Ga 1 − x N:Mg electron blocking layer on the emission characteristics of ultraviolet light‐emitting diodes has been investigated. The carrier injection in the light‐emitting diodes is simulated and compared with electroluminescence measurements. The light output power depends strongly on the aluminum mole fraction x as well as on the magnesium supply in the vapor phase during the growth of the Al x Ga 1 − x N:Mg electron blocking layer. The highest output power has been found for an aluminum content x of around 44% and an Mg/III‐ratio of 3.0% for light‐emitting diodes with an emission wavelength near 320 nm. This effect can be attributed to an improved carrier injection and confinement preventing electron leakage into the p‐doped layers of the light‐emitting diode and an effective hole injection into the active region.